Kurikulum Merdeka: Harapan Baru Bagi Pendidikan Indonesia - Hasdawaty, Ervinna (Journal of Innovation in Teaching and Instructional Media, 2025)
The Independent Curriculum is here as a response to the demands of educational transformation in the contemporary era. This study aims to analyze the implementation of the Independent Curriculum as an effort to renew the national education system. Using a qualitative research method with a literature study approach, this study examines various aspects of the implementation of the independent curriculum. The results of the study show significant transformations in several aspects: (1) a shift in the learning paradigm that increases student engagement by 76%, (2) an increase in problem-solving skills through project-based learning by 45%, (3) adoption of learning technology reaches 78.5%, (4) an increase in parental involvement by 65%, and (5) teacher competency development shows an increase of 67%. The main challenges include the digital divide, teacher readiness, and equal access. Recommendations include strengthening technological infrastructure, ongoing professional development, and a support system for educational tri-center collaboration.